Causality between energy consumption and economic growth in the V4 countries - Krkošková, Radmila (Technological and Economic Development of Economy, 2021)
Energy plays an important role in economic development. This paper deals with the long-run relationship between energy consumption and real GDP for V4 countries from 2005 to 2019. The analysis was based on the unit root tests, co-integration tests, and causality tests. There are two questions. The first question is if energy consumption the stimulus to GDP, resp. energy consumption causes GDP. And the second question is if GDP the stimulus for energy consumption, resp. GDP causes consumption of energy. Energy consumption has an essential role in the economy on both the demand and the supply. It means that there should be a causal relationship from energy consumption to GDP as well as vice versa. Given that in the long run the energy consumption Granger causes the GDP in Slovakia, Hungary, and the Czech Republic, it means that energy consumption could cause economic growth in these countries. The only country where no significant relationship between energy consumption and the GDP has been demonstrated in Poland.